Effects of psilocybin, psychedelic mushroom extract and 5-hydroxytryptophan on brain immediate early gene expression: Interaction with serotonergic receptor modulators - Lerer, Elad; Botvinnik, Alexander; Shahar, Orr; Grad, Meitar; Blakolmer, Karin; Shomron, Noam; Lotan, Amit; Lerer, Bernard; Lifschytz, Tzuri (Frontiers in Pharmacology, 2024)
Immediate early genes (IEGs) are rapidly activated and initiate diverse cellular processes including neuroplasticity. We report the effect of psilocybin (PSIL), PSIL-containing psychedelic mushroom extract (PME) and 5-hydroxytryptophan (5-HTP) on expression of the IEGs, cfos, egr1, and egr2 in mouse somatosensory cortex (SSC). In the initial experiment, male C57Bl/6j mice were injected with PSIL 4.4mg/kg or 5-HTP 200mg/kg, alone or immediately preceded by serotonergic receptor modulators. IEG mRNA expression one hour later was determined by real time qPCR. PSIL but not 5-HTP significantly increased expression of all three IEGs. In a replication study, in which a group of mice treated with PME was added, PSIL and PME upregulated levels of egr1 and cfos, while the upregulation of egr2 was not significant. No correlation was observed between the head twitch response (HTR) induced by PSIL and its effect on the IEGs. The serotonergic receptor modulators did not significantly alter PSIL-induced IEG expression, with the exception of the 5-HT2C antagonist )RS102221(, which significantly enhanced PSIL-induced egr2 expression. 5-HTP, at a dose sufficient to induce significant HTR, did not affect any of the IEGs. We have shown that PSIL and PME but not 5-HTP induced a significant increase in cfos and egr1 expression in mouse SSC. Our findings suggest that egr1 and cfos expression may be associated with psychedelic effects.